2019
DOI: 10.23937/2474-3658/1510071
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus in Tunisia: Results of a Multicenter Study

Abstract: Background: Methicillin resistant Staphylococcus aureus (MRSA) as a major cause of infections in hospital and community settings is a global health concern. The purpose of this study was to determine the antimicrobial susceptibility and the molecular characteristics of MRSA strains causing community-acquired (CA) and hospital-acquired (HA) infections in Tunisia.Methods: A total of 135 non-duplicate MRSA strains were consecutively collected from five Tunisian hospitals. Antimicrobial susceptibility was done by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
2
2
1
Order By: Relevance
“…In our study, all the MRSA isolates were susceptible to linezolid and tigecycline. The MIC 50 , MIC 90 and the mean MIC were similar to those reported in the previously study from Tunisia [21].…”
Section: Figure1 Population Analysis Profile Curves Of Four Isolatessupporting
confidence: 87%
See 3 more Smart Citations
“…In our study, all the MRSA isolates were susceptible to linezolid and tigecycline. The MIC 50 , MIC 90 and the mean MIC were similar to those reported in the previously study from Tunisia [21].…”
Section: Figure1 Population Analysis Profile Curves Of Four Isolatessupporting
confidence: 87%
“…Our study documented the presence of 0.6% hVISA and 2.5% teicoplanin resistance amongst MRSA isolates. The previously study in Tunisia reported hVISA and teicoplanin resistance prevalence of 0.8% [21]. No resistance to vancomycin was noted in our study and in Tunisia [21].…”
Section: Figure1 Population Analysis Profile Curves Of Four Isolatessupporting
confidence: 50%
See 2 more Smart Citations
“…Moreover, strains clustered within a single pulso-type also showed similar antimicrobial resistance properties. Other studies have also highlighted correlations between strain relatedness and antimicrobial resistance patterns [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%